Promoting Good Health and Well-being: Essential in Leading to Up-gradation of Living Conditions (International Journal of Preventive Medicine and Health (IJPMH), 2025)
The main objective of this research paper is to generate information regarding the meaning and significance of promoting good health and well-being. Individuals belonging to all age groups, occupations, communities, and socio-economic backgrounds need to augment information regarding various factors that promote good health and well-being, both physically and psychologically. All types of factors are required to be put into operation in a well-organised and regimented manner. In other words, positivity needs to be reinforced in all the factors. It is understood that leading to the up-gradation of overall living conditions is regarded as one of the primary goals for individuals, belonging to all communities and socio-economic backgrounds. To achieve this goal, one must consider several factors, i.e. education, careers, employment opportunities, resources, assets, property, health, well-being, family, relationships, personality traits and overall living conditions. All factors must be implemented adequately, so one will be physically and psychologically healthy. Hence, to carry out all tasks and activities in a successful manner, one may not be free from health problems and illnesses, but one needs to be psychologically sound. Therefore, it is well understood that promoting good health and well-being is essential to improving living conditions. The main concepts considered in this research paper are understanding the meaning and significance of promoting good health and well-being, measures to be put into practice in promoting good health and well-being and advantages of promoting good health and well-being.